Utilization of Al-Islam Instructional Material in Islamic Religious Education - Maulana, Rohasib; Syadiri, Saifuddin; Sabara, Rahma (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
Muhammadiyah, one of Indonesia's Islamic organizations, has long been involved in education and strives to stay up with scientific and technological advancements. One of the initiatives and materials generated is for Islamic religious education, which is being used at Muhammadiyah 8 Elementary School in Surabaya, East Java. Muhammadiyah 8 Elementary School Surabaya formulates instructional materials in one instructional material called Al-Islam to suit the community's needs and improve Islamology. Al-Islam instructional material are one of the distinguishing features of Muhammadiyah educational institutions. It covers every aspect of Islamic religious education, including moral creed, jurisprudence, Koranic study and interpretation, Hadith studies, Islamic history, and Arabic. This study aims to examine the learning outcomes at Muhammadiyah 8 Elementary School in Surabaya, where the instructional materials incorporate Al-Islam. This study is qualitative. Specifically, descriptive research reveals observations, interviews, and documentation outcomes. According to the findings, Muhammadiyah 8 Elementary School Surabaya has its own instructional materials for developing and teaching Islamic religious education subjects to students, known as Al-Islam. By using Al-Islam instructional material, students' knowledge and potential in Islamic religious education will develop holistically and comprehensively. Muhammadiyah 8 Surabaya Elementary School strives to distribute Islamic religious education subjects within the framework of Al-Islam so that students can master Islamic religious education subjects in an integrated and interdisciplinary manner, based on kaffah human beings who are pious ritualists and socially.Kata Kunci: Pembelajaran, Interdisipliner, Bahan Ajar al-Islam, SD Muhammadiyah.